Flipped Classroom Research and Trends from Different Fields of Study - Zainuddin, Zamzami; Halili, Siti Hajar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This paper aims to analyse the trends and contents of flipped classroom research based on 20 articles that report on flipped learning classroom initiatives from 2013–2015. The content analysis was used as a methodology to investigate methodologies, area of studies, technology tools or online platforms, the most frequently keywords used and works cited references, impacts for students’ learning, and flipped classroom challenges. The results of the analysis were interpreted using descriptive analysis, percentages, and frequencies. This analysis found that various fields were practiced in the flipped classroom approach, and some technology tools were used as the online platform for its practice. Analysis of the impacts showed that flipped classroom brought positive impacts toward students’ learning activities such as achievement, motivation, engagement, and interaction. Several issues in this discussion become implications that can be taken into consideration for future research. Some challenges found in applying flipped classroom are needed to be addressed by future researchers, such as suitability of the flipped classroom for poor quality of video lectures and untrained instructor. This study also becomes an implication for government or policymakers to determine the flipped classroom as a contemporary model to be implemented in teaching-learning activities for higher education, even K-12 students.